Os impactos da internet sobre os processos de mobilização política: uma análise da campanha da ficha limpa - Guisordi, Patricia Cucio (2017)
Observing the increasing use of Internet devices in the political mobilizations of the early 21st century, it is noted that social movements have changed and started to use other means and resources to influence their policies in the public sphere. Understanding this is a global phenomenon and, especially since the 2013 June Jouneys, it also occurs in Brazil, this research sought to understand how social movements use cyberactivism to include their demands in the arenas of Brazilian institutional politics. For this, a case study of the political mobilization on the Internet was carried out in favor of the Ficha Limpa “Clean Record” analyzing the publications that the members of the Movement to Combat Electoral Corruption, performed in the Community of Orkut MCCE Ficha Limpa and the sites that were cited as source of information by the members of the same. In order to qualify the data collected through the mapping and the bibliographical survey, in-depth interviews were conducted with individuals belonging to the National Committee of the Ficha Limpa Campaign, members of the Orkut Community, and with the Avaaz Campaign Coordinator at the time. Through this analysis, it can be verified that cyberactivism contributed to the inclusion of new guidelines in the political arena, but, on the other hand, that it is not the only who guarantees the success of the movement